Foraminifera from the lower Eocene Sakesar Limestone at Nammal, western Salt Range, northern Pakistan - Sameeni, S. J.; Butt, A. A. (Journal of Nepal Geological Society, 1997)
Study of the Sakesar Limestone of the lower Eocene age in the Nammal Gorge in western Salt Range is carried out. During the field investigation eight samples were collected from an 80 ft. thick limestone horizon, at equal interval. A new Alveolinid, foraminifera assemblage is identified.